2015
DOI: 10.4236/ojrad.2015.51003
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Brain Ventricles in Normal Subjects Using Computerized Tomography

Abstract: Background and Aim: As ageing advances, the human brain undergoes many gross and histopathological changes with regression of the brain tissue leading to the enlargement of the ventricles. Knowledge of morphometric and size of normal ventricular system of brain is important to understand these changes. Methods: For the present perspective study, computerized tomography (CT) for 152 patients (Males-89 and Females-63) were studied for the measurements of fourth ventricle, third ventricle and lateral ventricle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Comparing between male and female, M > F by 2 mm in study reported by D'Souza e dias Madora et al [2] and Moawia Gameraddin et al [4], 0.9 mm in present study and equal in study by Brij Raj Singh et al [3].…”
Section: Author Male Femalesupporting
confidence: 48%
See 1 more Smart Citation
“…Comparing between male and female, M > F by 2 mm in study reported by D'Souza e dias Madora et al [2] and Moawia Gameraddin et al [4], 0.9 mm in present study and equal in study by Brij Raj Singh et al [3].…”
Section: Author Male Femalesupporting
confidence: 48%
“…Morphometric studies of human brain ventricles have been under focus by many scholars due to the relation with pathologies evidences such as hydrocephalus, schizophrenia, tumor, trauma, etc., as well as gender and aging which could lead to dementia and or brain geriatrics. The advent of CT scanning resolved the problem of volumetric measurements performed on normal subjects [4]. Knowledge of normal variations in ventricular morphological features is important in endoscopic neurosurgery.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the skull was measured between the glabela (gl) and opisthocranion (op), skull height was measured between bregma (br) and basion (ba), and the width (transverse diameter) was measured between eurion (eu) of the right and left sides (►Figs. [1][2][3]. The cranial index (CI) was calculated as a ratio of the length of the skull to the transverse diameter percentagewise according to standard anatomical descriptions: 11,12 CI ¼ skull length/skull height  100.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 This scientific issue was addressed by many researchers recently. 3 Although the variability of the parameters of the ventricular system is extremely important, especially in the neurosurgery field, there is still a lack of the sources providing precise, unambiguous, or bias data on the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…In diencephalon of the forebrain the third ventricle (TV) is located between the right and left thalamus; whereas, the fourth ventricle (FV) which is a large tent-shaped is settled between cerebellum and brainstem. Moreover, it corresponds to at the back of the pons and top half part of the medulla oblangata in the hindbrain (Mavridis, 2014;Gameraddin et al, 2015). The FV linked with the third ventricle via cerebral aqueduct (aqueduct of Sylvius), and caudally via the median aperture (foramen of Magendie) with vallecula cerebelli and cisterna magna with the spinal canal and laterally, via the lateral aperture (foramina of Luschka) with the cerebellopontine angles (Mavridis).…”
Section: Introductionmentioning
confidence: 99%